Anti-CCL2 therapy reduces oxygen toxicity to the immature lung - Tayyab Shahzad; Ying Dong; Nina K. Behnke; Julia Brandner; Anne Hilgendorff; Cho-Ming Chao; Judith Behnke; Saverio Bellusci; Harald Ehrhardt (Cell Death Discovery, 2024)
Abstract Oxygen toxicity constitutes a key contributor to bronchopulmonary dysplasia (BPD). Critical step in the pathogenesis of BPD is the inflammatory response in the immature lung with the release of pro-inflammatory cytokines and the influx of innate immune cells. Identification of efficient therapies to alleviate the inflammatory response remains an unmet research priority. First, we studied macrophage and neutrophil profiles in tracheal aspirates of n = 103 preterm infants <29 weeks´ gestation requiring mechanical ventilation. While no differences were present at birth, a higher fraction of macrophages, the predominance of the CD14+CD16+ subtype on day 5 of life was associated with moderate/severe BPD. Newborn CCL-2−/− mice insufficient in pulmonary macrophage recruitment had a reduced influx of neutrophils, lower apoptosis induction in the pulmonary tissue and better-preserved lung morphometry with higher counts of type II cells, mesenchymal stem cells and vascular endothelial cells when exposed to hyperoxia for 7 days. To study the benefit of a targeted approach to prevent the pulmonary influx of macrophages, wildtype mice were repeatedly treated with CCL-2 blocking antibodies while exposed to hyperoxia for 7 days. Congruent with the results in CCL-2−/− animals, the therapeutic intervention reduced the pulmonary inflammatory response, attenuated cell death in the lung tissue and better-preserved lung morphometry. Overall, our preclinical and clinical datasets document the predominant role of macrophage recruitment to the pathogenesis of BPD and establish the abrogation of CCL-2 function as novel approach to protect the immature lung from hyperoxic injury.